Late Onset Hypocalcemia Caused by Hypovitaminosis D - Dini Anggini; Eka Agustia Rini (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: hypocalcemia is a common metabolic problem in neonates and infants that can be life threatening. The incidence of hypocalcemia leads to complications and developmental disorders in children. Case presentations: A 1 month-old boy with hypovitaminosis D and a history of recurrent hypocalcemia since one week of age. The patient had repeated seizures at the age of 7 days without fever and hypoglycemia, the overall physical examination was within normal, the results of the lumbar puncture were within normal limits. Laboratory examinations at that time showed low of serum calcium, urinary calcium, calcium ion and vitamin D levels, while magnesium, phosphorus and parathyroid hormone (PTH) levels were within normal limits. The patient was diagnosed with late onset hypocalcemia caused by hypovitaminosis D. The patient was given vitamin D therapy, calcium lactate, and intravena calcium correction was performed. Conclusion: late onset hypocalcemia occurring after the first 7 days of life was associated with hyperparathyroidism, high phosphate formula administration, DiGeorge syndrome, hypomagnesemia, and vitamin D deficiency.